Hemoglobin-mediated nitric oxide signaling - Helms, Christine (2013)
The rate that hemoglobin reacts with nitric oxide (NO) is limited by how fast NO can diffuse into the heme pocket. The reaction is as fast as any ligand/protein reaction can be and the result, when hemoglobin is in its oxygenated form, is formation of nitrate in what is known as the dioxygenation reaction. As nitrate, at the concentrations made through the dioxygenation reaction, is biologically inert, the only role hemoglobin was once thought to play in NO signaling was to inhibit it. However, there are now several mechanisms that have been discovered by which hemoglobin may preserve, control, and even create NO activity. These mechanisms involve compartmentalization of reacting species and conversion of NO from or into other species such as nitrosothiols or nitrite which could transport NO activity. Despite the tremendous amount of work devoted to this field, major questions concerning precise mechanisms of NO activity preservation as well as if and how Hb creates NO activity remain unanswered.